Towards de-dairyfication of the diet?—Consumers downshifting milk, yet justifying their dairy pleasures - Autio, Minna; Sekki, Sanna; Autio, Jaakko; Peltonen, Katja; Niva, Mari (Frontiers in Sustainability, 2023)
Currently, the consumption of liquid milk in the Western European countries and the US is declining. At the same time, the consumption of other dairy products, e.g., cheese and sour-milk products, is increasing. Dairy production together with meat production is one of the main food sources of greenhouse gases causing climate change. Thus, transition towards more sustainable diets requires reduction of both meat and dairy products. Consumers who do not use milk (e.g., vegans) have gained more scholarly attention compared to those who are reducing milk consumption. Our study focuses on Finnish consumers who have reduced the use of cow’s milk but not have abandoned dairy entirely. Through qualitative data we analyse how consumers narrate their detachment from using milk, how they justify their ongoing use of dairy products and how they see animal ethical issues as part of their eating practices. The results show that consumers began their dietary change by first reducing meat eating, and only then milk. Cheese eating was an enjoyment that was difficult to resist and to replace with plant-based alternatives. Although the consumers recognised the interdependence between meat and milk production and consumption, at the level of everyday practices the giving up of milk proved more challenging than giving up meat. We argue that the declining use of fluid milk contributes to the de-dairyfication of eating habits, but obstacles remain in reducing the consumption of other dairy products.